2000
DOI: 10.1128/jvi.74.16.7331-7337.2000
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Expression in a Human Cell Line Stably Transduced with Herpesvirus Saimiri

Abstract: Herpesvirus saimiri (HVS) is the prototype gamma-2 herpesvirus; it has significant homology to the human gammaherpesviruses Kaposi's sarcoma-associated virus and Epstein-Barr virus and the murine gammaherpesvirus murine herpesvirus 68. HVS causes a persistent asymptomatic infection in its natural host, the squirrel monkey. Both subgroups A and C possess the ability to immortalize common marmoset T lymphocytes to interleukin-2-independent proliferation. However, only subgroup C is capable of transforming human,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 60 publications
1
56
1
Order By: Relevance
“…We and others have previously demonstrated that HVS can infect a wide range of human cell lines and that the HVS genome persists in a latent episomal state that segregates to progeny upon cell division allowing longterm in vitro gene expression. [7][8][9][10][11] More recently, we demonstrated that the HVS genome can persist in human tumor xenografts derived from ex vivo HVS-infected human carcinoma cells. 12,19 Our previous work has demonstrated that HVS-based vectors (expressing GFP) persisted as nonintegrated episomes in vivo, and provided long-term transgene expression with no evidence of promoter silencing, viral spread or cytopathic effects.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We and others have previously demonstrated that HVS can infect a wide range of human cell lines and that the HVS genome persists in a latent episomal state that segregates to progeny upon cell division allowing longterm in vitro gene expression. [7][8][9][10][11] More recently, we demonstrated that the HVS genome can persist in human tumor xenografts derived from ex vivo HVS-infected human carcinoma cells. 12,19 Our previous work has demonstrated that HVS-based vectors (expressing GFP) persisted as nonintegrated episomes in vivo, and provided long-term transgene expression with no evidence of promoter silencing, viral spread or cytopathic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Specific amplification of the ORF 73, a gene latently expressed in human carcinoma cell lines, 11 was performed. In addition, as a suitable control, GAPDH DNA was detected in all samples, indicating that sufficient amounts of DNA had been extracted from each tissue.…”
Section: Efficient Infection Of Human Tumor Xenografts Via Direct Intmentioning
confidence: 99%
See 3 more Smart Citations